Thin-film transducers for the detection and imaging of Brillouin oscillations in transmission on cultured cells - Perez-Cota, Fernando; Smith, Richard J.; Moradi, Emilia; Webb, Kevin F.; Clark, Matt (IOP Publishing, 2015)
Mechanical imaging and characterisation of biological cells has been a subject of interest for the last twenty years. Ultrasonic imaging based on the scanning acoustic microscope (SAM) and mechanical probing have been extensively reported. Large acoustic attenuation at high frequencies and the use of conventional piezo-electric transducers limit the operational frequency of a SAM. This limitation results in lower resolution compared to an optical microscope. Direct mechanical probing in the form of applied stress by contacting probes causes stress to cells and exhibits poor depth resolution. More recently, laser ultrasound has been reported to detect ultrasound in the GHz range via Brillouin oscillations on biological cells. This technique offers a promising new high resolution acoustic cell imaging technique. In this work, we propose, design and apply a thin-film based opto-acoustic transducer for the detection in transmission of Brillouin oscillations on cells. The transducer is used to generate acoustic waves, protect the cells from laser radiation and enhance signal-to-noise ratio (SNR). Experimental traces are presented in water films as well as images of the Brillouin frequency of phantom and fixed 3T3 fibroblast cells.